Physician Assistant Educator Competencies. Issue 1 (March 2019) - Zaweski, Joseph; Melcher, Betsy Quick; Sedrak, Mona; Von, Mary; Fletcher, Sara
Abstract : Abstract: The rapid expansion of physician assistant (PA) programs over the past decade has led to a shortage of experienced PA faculty. This has prompted many faculty development initiatives to help provide the skills needed by new faculty making the jump from clinical practice to academia. Faculty development is a key necessity in health professions education because many of the professionals attracted to the educator role are primarily trained as clinicians. Although this issue has been extensively evaluated by our colleagues in medical, nursing, and health education and various faculty development interventions have been implemented, this has not been done in the PA profession. In an effort to correct this, the Physician Assistant Education Association assembled a task force of experienced PA educators and charged them to evaluate the literature on faculty competencies in health professions education and to develop a set of PA educator competencies to help codify the essential knowledge, skills, attitudes, and behaviors that faculty need to be successful in their academic roles. The task force met its charge by engaging in an extensive review of the literature, developing a competency framework and proposed competencies, and soliciting the input of a diverse panel of experts in PA education to vet the proposed competencies. Using the insights and recommendations from the expert panel, the task force refined the competencies—resulting in the framework of PA educator competencies presented in this document.